When journalists lose their foothold: Swedish and Norwegian verification scandals in #Metoo-movement coverage - Allern, Sigurd; Pollack, Ester (Journalistica, 2021)
The global #MeToo movement exposed the widespread structural problem of sexual harassment, which was also the case in Sweden and Norway. Across the various sectors of working life, women were able to identify with the call. This perspective, however, was under- mined in the public sphere when person-centred scandal stories about a few powerholders and media celebrities took over. In addition, a lack of verifiable documentation – and uncritical use of anonymous sources – ignited renewed debates about the ethical standards of professional journalism. This article discusses two alleged #MeToo cases: Aftonbladet’s dramatic and unfounded accusations against the theatre CEO Benny Fredriksson and VG’s misuse and manipulation of a “bar-dance” episode involving the Norwegian Labour politician Trond Giske. Both media stories developed into “critical incidents”, resulting in public criticism, self-examination and discussions around ethical rules and regulation.